2012
DOI: 10.15369/sujms.24.77
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Correlation between Gd-EOB-DTPA-enhanced MRI Using the 3T MRI System and Tc-99m-GSA Hepatic Scintigraphy/Hepatic Function Tests in Prehepatectomy Cases

Abstract: This study compared results from Gd-EOB-DTPA on two different phases of 3T MRI with those from Tc-99m-GSA hepatic scintigraphy and hepatic function tests. Twenty-four patients with liver tumor were included in this study. All patients underwent Gd-EOB-DTPA-enhanced-MRI and Tc-99m-GSA hepatic scintigraphy. Clearance index HH15 and receptor index LHL15 were calculated for the Tc-99m-GSA, while signal intensities SI of liver at pre-injection and at 4 / 20 min post-injection, and of spleen at 4 min / 20 min were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Therefore, we can assume that this washout is also occurring in the liver ECF space at 20 min after intravenous injection. A previous study that measured the LSC at 20 min after intravenous injection reported that the correlation between the LSC and HH15, which represents the retention of 99m Tc-GSA in the blood [5], was stronger than that between the LSC and LHL15 [12,13]. This fact may indicate that the LSC at 20 min after intravenous injection re ects enhancement by the Gd-EOB-DTPA remaining in liver ECF space rather than in the hepatocytes.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Therefore, we can assume that this washout is also occurring in the liver ECF space at 20 min after intravenous injection. A previous study that measured the LSC at 20 min after intravenous injection reported that the correlation between the LSC and HH15, which represents the retention of 99m Tc-GSA in the blood [5], was stronger than that between the LSC and LHL15 [12,13]. This fact may indicate that the LSC at 20 min after intravenous injection re ects enhancement by the Gd-EOB-DTPA remaining in liver ECF space rather than in the hepatocytes.…”
Section: Discussionmentioning
confidence: 95%
“…Clinicians can easily appraise a patient's liver function by converting the LSC into the LHL15, because the evaluation standards of the HH15 and LHL15 have been supported for many years [14]. However, most studies that examined the correlation between the LSC and LHL15 did not have su ciently large sample sizes [11][12][13]. In addition, the results of these correlation analyses remain controversial from the standpoint of the differences in uptake and excretion between Gd-EOB-DTPA and 99m Tc-GSA [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations